2022
DOI: 10.1177/00207640221077015
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of burnout in medical students in Guatemala: Before and during Covid-19 pandemic comparison

Abstract: Burnout is a syndrome consisting of physical, emotional, and mental exhaustion along with depersonalization and poor sense of personal accomplishment. Often related to work conditions. Several recent studies from around the world have shown high rates of burnout among medical students in different countries. In Guatemala City, we decided to assess levels of burnout in 2017 and then again in December 2020. In the first wave from one private medical school, we had a total of 159 respondents (response rate of 56.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…For example, 68% of medical students in Australia reported a deterioration of their mental well-being after the beginning of the COVID-19 pandemic (Lyons et al, 2020). Similar data have been reported in Pakistan (Noreen et al, 2020) or Guatemala with an increase of burnout symptoms (Ruiz et al, 2022). A study on the psycho-emotional well-being of medical students in Kazakhstan under the COVID-19 pandemic reported the presence of anxiety and depression symptoms at HADS in 39.0% and 40.6% of students, respectively; also, clinically significant levels of anxiety and depression were detected in 19.4% and 16.1% of students, respectively (Popova et al, 2021).…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…For example, 68% of medical students in Australia reported a deterioration of their mental well-being after the beginning of the COVID-19 pandemic (Lyons et al, 2020). Similar data have been reported in Pakistan (Noreen et al, 2020) or Guatemala with an increase of burnout symptoms (Ruiz et al, 2022). A study on the psycho-emotional well-being of medical students in Kazakhstan under the COVID-19 pandemic reported the presence of anxiety and depression symptoms at HADS in 39.0% and 40.6% of students, respectively; also, clinically significant levels of anxiety and depression were detected in 19.4% and 16.1% of students, respectively (Popova et al, 2021).…”
Section: Introductionsupporting
confidence: 87%
“…All the discussed evidences suggest the need of implementing programs to increase resilience to emotional stress among medical students (Avilov & Galiulina, 2020). All efforts should be made to prevent consequences of burnout, poor psychological well-being in future medical professionals (Chumakov et al, 2022; Ruiz et al, 2022; Watson et al, 2020). Medical schools should implement programs in order to manage stress, identify students at risk for developing mental disorders, and ensure easy access to specialized mental health services (Kasimova et al, 2018; Ruzhenkova, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Absence of burnout assessment before the COVID-19 pandemic in Belize does not allow for comparison with pre-pandemic estimates. In the neighboring country of Guatemala, a study that assessed burnout in medical students found that rates of burnout were high and increased during the pandemic, when compared to pre-pandemic levels ( Ruiz et al, 2022 ). This is in line with recent studies, which confirm similar trends ( Morgantini et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%